2021
DOI: 10.1007/s40744-020-00272-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics and Indicators of Treatment Initiation with Repository Corticotropin Injection in Patients with Rheumatoid Arthritis: A Claims Database Analysis

Abstract: Repository corticotropin injection (RCI) is indicated as adjunctive, short-term therapy in selected patients with RA. To characterize RCI users and identify predictors of RCI initiation in RA, we compared preindex characteristics, treatment patterns, comorbidities, healthcare resource utilization (HCRU), and costs for patients who had initiated RCI treatment (RCI cohort) versus patients with no RCI claims and ≥ 1 targeted synthetic or biologic disease-modifying antirheumatic drugs (ts/bDMARD) claim (non-RCI ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“… 20 Another analysis of a rheumatology electronic medical record (EMR) database reported significant improvements in RA disease activity, functional status and pain with a decreased need for concomitant medications for up to 1 year following initiation of RCI therapy. 21 The benefit–risk profile of RCI is consistent across well-controlled clinical trials, 4 open-label studies 1 , 13 15 and a retrospective analysis. 20 The current study provides additional supportive real-world rheumatology practice data on disease-assessment and prescribing patterns, dosing, clinical effectiveness and tolerability, which are important for understanding performance in patients with complex disease in clinical practice.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“… 20 Another analysis of a rheumatology electronic medical record (EMR) database reported significant improvements in RA disease activity, functional status and pain with a decreased need for concomitant medications for up to 1 year following initiation of RCI therapy. 21 The benefit–risk profile of RCI is consistent across well-controlled clinical trials, 4 open-label studies 1 , 13 15 and a retrospective analysis. 20 The current study provides additional supportive real-world rheumatology practice data on disease-assessment and prescribing patterns, dosing, clinical effectiveness and tolerability, which are important for understanding performance in patients with complex disease in clinical practice.…”
Section: Introductionmentioning
confidence: 66%
“…Rheumatoid arthritis (RA) is an autoimmune disease that causes synovial inflammation and progressive joint damage. 1 There is a large unmet need for patients with refractory RA who display persistently high RA disease activity or flares despite treatment with standard-of-care therapies. 1 Real-world evidence is necessary to support the effectiveness of RA drugs in a clinical setting and to identify appropriate patient populations who are likely to experience a clinical response to such treatments.…”
Section: Introductionmentioning
confidence: 99%
“…28 Additional real-world outcome studies show that osteoarthritis is a prevalent comorbidity in patients with RA treated with RCI. 15,29,30 In addition, the presence of more tender than swollen joints may reflect the coexistence of osteoarthritis in this patient population. 31 Clinical measures of disease severity, including CDAI and number of tender or swollen joints, indicated that patients had high RA activity prior to starting RCI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…RCI is used in patients experiencing acute episodes or exacerbations of RA, as a late-line therapy to treat RA flares, as a bridge to new therapy, or as an add-on to prior therapy. 6 , 15 Multiple published studies of RCI use in patients with refractory RA support its efficacy and safety including patient-reported improvements in pain, fatigue, and work productivity; 16−20 however, there remains a need for real-world evidence for the use of RCI to treat RA. Namely, data on prescribing patterns, dosing, efficacy, and tolerability are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous available DMARDs, in the majority of patients, LDA is not achieved or maintained over a prolonged period [6,7]. An estimated 6% of patients with moderate to severe RA (approximately 30,000-34,000 US patients) do not respond to DMARDs [8][9][10]. Failure to achieve LDA and possibly remission can lead to irreversible joint damage [6].…”
Section: Introductionmentioning
confidence: 99%